2017
DOI: 10.3329/bjvm.v14i2.31399
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors Associated With Neospora Caninum in Dairy Cattle of Western Dairy Pocket Area in Chitwan District of Nepal

Abstract: Dairy industry is growing in Nepal and western dairy pocket area is the main milk producing area in Chitwan district. This study was carried out to determine the seroprevalence and risk factors associated with N. caninum in western dairy pocket area in Chitwan district of Nepal. A cross-sectional study was conducted from April 2014 to July 2014 among the small holder dairy farms, and out of 2188 animals from different sampling villages, 186 (8.5%) animals were randomly selected. Individual blood samples (5-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
3
4
0
Order By: Relevance
“…The results obtained were statistically analyzed and found that the seropositivity of N. caninum antibodies in different age groups were statistically non-significant. This result is in accordance with the findings of Yadav et al (2016). Llano et al (2018) and Serrano-Martinez et al (2019) also reported that 3-5 age groups of animals were at more risk to the infection when compared to other age groups.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results obtained were statistically analyzed and found that the seropositivity of N. caninum antibodies in different age groups were statistically non-significant. This result is in accordance with the findings of Yadav et al (2016). Llano et al (2018) and Serrano-Martinez et al (2019) also reported that 3-5 age groups of animals were at more risk to the infection when compared to other age groups.…”
Section: Resultssupporting
confidence: 91%
“…This may be due to the immune system of pregnant animals which is more exposed to N. caninum during middle and last trimester of pregnancy rather than first trimester (Abdeltif et al, 2022). Several other studies also reported association of abortion history with seroprevalence of N. caninum (Sengupta et al, 2013;Yadav et al, 2016;Noori et al, 2019;Llano et al (2018;Miroud et al, 2019;Changoluisa et al, 2019;Mahajan et al (2019). The multiparous animals exhibited higher seropositivity (41.07%) for neosporosis in comparison to primiparous (23.81%) bovines.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, the overall seroprevalence was 5% in cattle managed in pastoral production systems. This finding was comparable with findings from Korea (4.1%), 20 Tanzania (4.5%), 21 Nepal (4.84%), 22 Japan (5.7%), 23 and the Czech Republic (5.83%). 24 However, the prevalence was considerably lower than the previous findings in Ethiopia which range from 13.3% to 23.8% in cattle managed under intensive and semi-intensive animal production systems.…”
Section: Discussionsupporting
confidence: 88%
“… 38 However, in our current findings, the lower seroreaction in the free-range rearing system was quite contradicting with several previous findings. 1 , 22 , 38 The difference in prevalence observed in the current study could arise from the differences in sample size, where the number of samples used for this study was minimal. In addition, the lower prevalence might be associated with the duration of the study, where this study was conducted during harsh climate conditions and severe drought that may hinder the maintenance and sporulation of N. caninum oocysts.…”
Section: Discussionmentioning
confidence: 83%